Investigation of antioxidant activity and phytochemical constituents of Artocarpus altilis - Kamal, Tara; Zuberdi, Ahmad Muzammil; Abdullateef, Raji Akintunde; Omar, Muhammad Nor (Academic Journals, 2012)
The phytochemical screening study and the antioxidant activity test of the twigs of Artocarpus altilis has been done for the first time. The Artocarpus genus is known to produce a large number of secondary metabolites, and is specifically rich in phenylpropanoids such as flavonoids and flavones. Results of this study indicated that A. altilis (twigs) contain terpenoids, saponins, phenolic group, flavonoids, glycoside, steroids and tannins, while alkaloid test yielded negative result. Investigation on these chemical compounds was done using the standard technique for assay of phytochemical constituents, with modification. The dried plant was extracted by using soxhlet apparatus using three solvents namely hexane, dichloromethane (DCM) and methanol, and it was observed that the plant has a characteristic of antioxidant using DPPH assay. DCM extract of Artocarpus altilis has a remarkable antioxidant activity with an IC50 value of 0.015 mg/ml compared with the standard butylated hydroxytoluene (BHT). This finding supports the possibility of using this plant for medicinal treatments.